2013
DOI: 10.1007/s00436-013-3480-6
|View full text |Cite
|
Sign up to set email alerts
|

The molecular and morphometrical description of a new diplozoid species from the gills of the Garra rufa (Heckel, 1843) (Cyprinidae) from Turkey—including a commentary on taxonomic division of Diplozoidae

Abstract: The paper presents a description of Paradiplozoon bingolensis sp. n. from the gills of Garra rufa Heckel, 1843 (Cyprinidae) collected from the Göynük Stream, a tributary of the Murat River, Turkey. This is the first diplozoid species to be described from G. rufa. P. bingolensis is distinguished from the other valid species in the genus by the combination of the morphology of the sclerites of its clamps and by the size of the central hooks. Even molecular characterization based on variability of the second inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 21 publications
0
29
2
1
Order By: Relevance
“…This is incongruent with the polytomic topology inferred from 66 homologous series of morphological traits [32] and close relationship between Gastrocotylinea and Discocotylinea based on morphological characters and close relationship between Microcotylinea and Discocotylinea using large nuclear subunit ribosomal RNA gene [33]. The topology of the three Diplozoidae family genera, ( Eudiplozoon , ( Sindiplozoon , Paradiplozoon )), was also in disagreement with most previous studies [9, 12, 14], except for the ML topology in Gao et al [9]. In our phylogram, Paradiplozoon (Chinese) formed a sister group with Sindiplozoon (with a robust support value).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…This is incongruent with the polytomic topology inferred from 66 homologous series of morphological traits [32] and close relationship between Gastrocotylinea and Discocotylinea based on morphological characters and close relationship between Microcotylinea and Discocotylinea using large nuclear subunit ribosomal RNA gene [33]. The topology of the three Diplozoidae family genera, ( Eudiplozoon , ( Sindiplozoon , Paradiplozoon )), was also in disagreement with most previous studies [9, 12, 14], except for the ML topology in Gao et al [9]. In our phylogram, Paradiplozoon (Chinese) formed a sister group with Sindiplozoon (with a robust support value).…”
Section: Discussionmentioning
confidence: 58%
“…As a result of this host plasticity, wrong taxonomic conclusions are often reached when arbitrarily describing a diplozoid species using solely the criterion of host species. Examples of such artefacts are six Chinese Paradiplozoon species and two Inustiatus species, all of which parasitise on different hosts, but exhibit negligible interspecific genetic differentiation, which indicates that they are most likely conspecifics [3, 9, 12, 18]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent molecular phylogenetic evaluations of Diplozoidae representatives consistently confirmed that the chub parasite P. megan was clustered with the majority of European Paradiplozoon and Diplozoon species (Sicard et al 2003;Matejusová et al 2004;Gao et al 2007;Civáňová et al 2013;Avenant-Oldewage et al 2014). Within this assemblage, P. megan alone represented a well-supported fontal subcluster affiliated with the rest of a group formed into two lineages: the first comprising P. nagibinae, P. sapae, P. bliccae and D. paradoxum while the second one associating P. pavlovskii and D. homoion.…”
Section: Discussionmentioning
confidence: 79%
“…Systematics of the family remains problematic due to a relatively high interspecific similarity in morphological features and limited number of species included in molecular comparisons (Matejusová et al 2001;Gao et al 2007;Civáňová et al 2013;Avenant-Oldewage et al 2014). Therefore, supplementary approaches would help in the assessment of species delimitation and/or phylogeny.…”
Section: Introductionmentioning
confidence: 99%